1995
DOI: 10.1046/j.1365-313x.1995.08020167.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous targeting of pea glutathione reductase and of a bacterial fusion protein to chloroplasts and mitochondria in transgenic tobacco

Abstract: Summary N-terminal presequencas from cDNAs encoding mitochondrion-or chloroplast-specific proteins are able, with variable efficiencies, to target preprotsins to their respective organelles, in the few cases studied in which a nuclearencoded protein is found in both these orgeneiles, each compartment-specific isoform is encoded by a separate gene. Glutathione reductase (GR) from peas is encoded by a single nuclear gene and yet GR is distributed between chloroplasts, mitochondda and the cytosoL Previous sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
119
1
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(126 citation statements)
references
References 39 publications
2
119
1
4
Order By: Relevance
“…Chew et al (25) demonstrated dual targeting of ascorbate peroxidase (At4g08390), monodehydroascorbate reductase (At1g63940), and glutathione reductase (At3g54660) to both the plastid and mitochondrion, whereas a specific dehydroascorbate reductase (At3g54660) was solely imported into the mitochondria. The work extended previous investigations that suggested dual targeting of glutathione reductase (26) and solved the contradiction between reported activities of the respective enzyme activities in mitochondrial preparations and the lack of corresponding genes with unequivocal information for mitochondrial targeting in the Arabidopsis thaliana genome (27). Recently, PrxII F was identified as mitochondrial type II peroxiredoxin.…”
supporting
confidence: 73%
“…Chew et al (25) demonstrated dual targeting of ascorbate peroxidase (At4g08390), monodehydroascorbate reductase (At1g63940), and glutathione reductase (At3g54660) to both the plastid and mitochondrion, whereas a specific dehydroascorbate reductase (At3g54660) was solely imported into the mitochondria. The work extended previous investigations that suggested dual targeting of glutathione reductase (26) and solved the contradiction between reported activities of the respective enzyme activities in mitochondrial preparations and the lack of corresponding genes with unequivocal information for mitochondrial targeting in the Arabidopsis thaliana genome (27). Recently, PrxII F was identified as mitochondrial type II peroxiredoxin.…”
supporting
confidence: 73%
“…The first dual targeted protein identified in plants was the Pisum sativum (pea) glutathione reductase (GR) which was shown to be targeted to both mitochondria and chloroplasts. 1 Since then the number of proteins shown to be dual targeted in plants is more than 250 ( Table 1). Dual targeting can refer to a protein targeted to any two locations, such as mitochondria and chloroplasts, mitochondria and the nucleus, 2 mitochondria and peroxisomes, 3 mitochondria and cytoplasm, 4 mitochondria and endoplasmic reticulum, 5 mitochondria and golgi, 6 mitochondria and plasma…”
mentioning
confidence: 99%
“…On the other hand, the possibility exists that the same RNA polymerase (encoded by one nuclear gene) is targeted to both organelles. Thus, it has been demonstrated that the presequence of pea gluthathione reductase is capable of co-targeting this enzyme or a foreign protein simultaneously to chloroplasts and mitochondria in vivo (33). However, analysis of the C.album sequence by a knowledge-based system for prediction of protein targeting, PSORT (http://psort.nibb.ac.jp), does not reveal any features of the N-terminus consistent with targeting to plastids.…”
Section: Discussionmentioning
confidence: 99%